PERANCANGAN MEDIA PROMOSI CHRISNA HOME SPA & AROMATHERAPY SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Utami, Evi Farsiah; Fianto, Achmad Yanu Alif; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: Nowadays Cooperatives Small and Medium Enterprises product is one of the economics pillar in Indonesia, nevertheless the interest for Cooperatives Small and Medium Enterprises advancement is still lacking. One of the Cooperatives Small and Medium Enterprises product, Chrisna Home Spa & Aromatherapy, still does not have significant media promotion since the last 4 years. Chrisna Home Spa & Aromatherapy is a natural product which rarely known by society and being accused plagiarism because unintended similarities with other brand product packaging, Bali Ratih. This become the background to design Chrisna Home Spa & Aromatherapy promotion media which use Ayurveda therapy from India as its product base. As a distinctive effort, an icon or product character that represent each of the fragrance variant will done by manual drawing. Research method use qualitative method which done by doing interview, observation, documentation, and study literature to obtain data as a support to make promotion media design concept. The keyword that was found from promotion media design data analysis is âgracefulâ. So the media design use concept based on simplicity, luxurious, elegant, clean and modern as an elaboration from the previous keyword. The result from the promotion media is to introduce new image of Chrisna Home Spa & Aromatherapy product to society as solution for the previous problem.Â Keywords: Promotion Media, Aromatherapy, Spa, Icon, Brand AwarenessÂ Â